(untitled) (PALIMPSEST / ПАЛИМПСЕСТ, 2018)
This paper draws on a semiotic and semantic analysis of Vesna Mundishevska-Veljanovska’s poetry book “In the Cocoon of the Century” that is about to be published in Serbian language by the Center of Culture in Pozharevac, Serbia. The analysis sheds light on several semantic levels of specific lyric poems, as well as on several levels of abstract interpretation of meaning of the entire poetic endeavor. In addition, four elements come to the forefront: water, air, earth, and fire, which the poetess seems to have coded in her poetry spontaneously and unconsciously, by pointing to their synergy and interconnectedness in time and space, at both the physical and metaphysical level. The second part of the paper offers language analysis of the poetry code, i.e. the stylistic and versification features of the poems. Eventually, the paper concludes by highlighting the fact that the poetess’ code is original in terms of its manifestation, due to the presence of unexpected rhyme as well as sharp and rather shocking metaphors that penetrate reader’ consciousness, enabling their awakening and turning towards the really essential concepts.